Cinta: Objek dan Puisi (Konsep Cinta Erich Fromm dalam Puisi-puisi Karya W.S Rendra) - Adhea Tsabitah Sulistiyo; Syihabuddin Syihabuddin (Lembaga Pengembangan Kinerja Dosen, 2023)
Love can be used as an answer to the question of human existence. So many philosophers from the west and east offer concepts about love, Erich Fromm is one of them who considers that love is an art. The purpose of this study is to classify five objects of love from Erich Fromm's thoughts in poems by W.S Rendra. Poetry was chosen as the object of research because poetry can be used as a means for someone to express love. This research method is a literature study as well as a literature review. The results of this study are five titles of poems that represent the five objects of love. First, object of brotherly love entitled